PENINGKATAN KOMITMEN PROFESIONAL GURU SMP MELALUI PENGUATAN EFIKASI DIRI DAN BUDAYA ORGANISASI - Ida Zuraida; Rita Retnowati; rais Hidayat (JURNAL MANAJEMEN PENDIDIKAN, 2020)
IMPROVING THE PROFESSIONAL COMMITMENT OF SMP TEACHERS THROUGH STRENGTHENING SELF-EFFICATION AND ORGANIZATIONAL CULTUREThis study is intended to determine the efforts needed that can be implemented in order to improve the Professional Competence of Junior High School Teachers through a study of  relationship of Self-Efficacy and Organizational Culture in the Commissariat of Leuwiliang and Cibungbulang This research was conducted by using a  survey method of a correlational approach. The conclusions obtained were: 1). There was a significant positive relationship between self-efficacy and professional commitment where the correlation coefficient (ry1)was 0.853,  the regression equation Ŷ = 19.778 + 0.878X and coefficient of determination 0.783. 2). There was a significant positive relationship between organizational culture and professional commitment where the correlation coefficient (ry2) was 0.227 and a regression equation Ŷ = 119.436 + 0.266X2 and determination coefficient was 0.051. 3). There was a positive and significant relationship between self-efficacy and organizational culture and professional commitment where the correlation coefficient (ry12) was 0.853 and a regression equation Ŷ = 17.128 + 0.827x1 + 0.029x2. Determination coefficient was 0.728 4). There was a dominant relationship in self-efficacy (X1) of organizational culture (X2) on teacher professional commitment (Y),where the correlation coefficient of self-efficacy with professional commitment (ry1) was .0853. The correlation coefficient between organizational culture and professional commitment (ry2) was 0.227. 5). There were other factors that influencing or relating to increasing professional commitment, they were: a). transformational leadership, b). Organizational Citizenship Behavior (OCB), c). organizational climate, d). teacher motivation.self-efficacy; organizational culture; professional commitment